Knowledge, attitudes and perceptions of African parents in Sydney, Australia towards Human Papillomavirus vaccine - Nweke, Nkechi (Health Promotion & Physical Activity, 2025)
Vaccine uptake in children below 18 years of age is dependent on parental consent. This study seeks to report on the knowledge, attitudes and perceptions of African parents in Sydney, Australia towards Human Papillomavirus vaccine. Purpose: To determine the knowledge, attitudes, and perceptions of African parents in Sydney, Australia on the HPV vaccine. Materials and methods: A questionnaire directed at African parents of children aged 10 to 15 years old in Sydney Australia was distributed from April 2023 to October 2023. Results: A total of 31 respondents returned completed questionnaires. The parents had a high level of knowledge on HPV vaccine (74.2%). Perception towards the vaccine was positive with the majority (83.9%) agreeing to vaccine uptake following prior information and expressing willingness for their children to be vaccinated (61.3%). Attitudes towards the vaccine were found to be positive. Majority of the parents were certain that the vaccine was neither against their religious/moral beliefs (71.0%) nor for experimental purposes (64.5%). Conclusion: Overall, this study revealed that African parents in Sydney, Australia have a high level of knowledge on HPV vaccine, positive perceptions and positive attitudes towards HPV vaccine.